Hard rock dark biosphere and habitability - Escudero, Cristina; Amils, Ricardo (Frontiers in Astronomy and Space Sciences, 2023)
The discovery that most of the prokaryotic diversity and biomass on Earth resides in the deep subsurface, calls for an improved definition of habitability, which should consider the existence of dark biospheres in other planets and moons of the Solar System and beyond. The discovery of "interior liquid water worlds" on some ice moons with waterless surfaces has piqued wide astrobiological interest, but the sporadic mentions of the possibility of life in the deep subsurface of rocky planets in recent habitability reviews calls for a methodical effort to develop sufficient knowledge, both scientific and technological, to include the dark biospheres in our habitability assessments. In this review we analyze recent developments and the methodologies employed to characterize Earth's continental hard rock deep subsurface to both prepare the future exploration of the putative dark biosphere of Mars and to highlight its importance when evaluating planetary habitability.Habitability is defined as the potential of a given planetary environment to sustain life (Cockell et al, 2016 and references therein). Obviously, this concept depends on the conditions required for life to develop, among them energy, liquid solvent to facilitate mass transfer reactions and temperatures compatible with cell functions and the liquid state of the solvent (